Memperkaya Pembelajaran Agama Kristen: Strategi Integrasi Pemikiran Quintilianes dalam Proses Pengajaran Retorika Rohani - Elfin Warnius Waruwu Elfin; Dyulius Thomas Bilo Dyulius (Jurnal Pendidikan Agama dan Teologi, 2023)
Spiritual rhetoric has an important role in strengthening understanding and communication of religious teachings, but often does not receive sufficient attention in Christian religious education. The approach of Quintilianes, a famous philosopher and rhetorician from the ancient Roman era, provides a solid foundation for improving the teaching of spiritual rhetoric. This article presents key concepts from Quintilianes' thinking that can be adapted in the study of Christianity, such as the importance of ethics in communication, developing speaking skills, and emphasizing the formation of good character. This integration strategy can be applied in various contexts of Christian religious education, both in religious schools, churches and within the family environment. By incorporating elements of spiritual rhetoric into the curriculum, educators can help students understand and articulate their beliefs more effectively, while promoting fundamental moral and spiritual values. In facing the complexity of the contemporary world, the integration of Quintilianes' thoughts in the study of Christianity becomes increasingly relevant. This article proposes that this approach can provide a powerful foundation for increasing understanding, appreciation, and practice of Christianity, as well as fostering deeper spiritual growth in students.